1999
DOI: 10.1046/j.1365-2362.1999.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of WT1 mRNA in urine from patients with kidney diseases

Abstract: Detachment of glomerular epithelial cells (GEC) from glomerular basement membrane (GBM) could account for a part of the pathogenic mechanism of proteinuria seen in primary and secondary renal diseases. The Wilms' tumour suppresser gene (WT1) is strictly expressed in GEC in the adult kidney. Mutations of WT1 gene have been implicated in progressive renal damage. Utilizing nested RT-PCR we detected mRNA of WT1 in the urine of patients with renal diseases. Seven of 20 (35%) chronic glomerulonephritis (CGN), eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…Finally, there may be other factors that affect the level of urine exosomal WT-1 in patients, such as genetics, nutrition, or other environmental factors. An alternative method to detect urinary WT-1 does not require exosome isolation; as reported by Kubo et al (13), WT-1 mRNA was detected in urinary sediments from patients with various glomerular diseases, but the variability was apparently higher, and AUC analysis was not performed. Other noninvasive methods to evaluate podocyte-specific injury include counting numbers of podocytes in urine sediment by podocalyxin immunofluorescent staining (10), measuring the podocin/AQP2 mRNA ratio in urinary sediments (21), or assessing direct podocalyxin protein in whole urine with a self-developed ELISA kit (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there may be other factors that affect the level of urine exosomal WT-1 in patients, such as genetics, nutrition, or other environmental factors. An alternative method to detect urinary WT-1 does not require exosome isolation; as reported by Kubo et al (13), WT-1 mRNA was detected in urinary sediments from patients with various glomerular diseases, but the variability was apparently higher, and AUC analysis was not performed. Other noninvasive methods to evaluate podocyte-specific injury include counting numbers of podocytes in urine sediment by podocalyxin immunofluorescent staining (10), measuring the podocin/AQP2 mRNA ratio in urinary sediments (21), or assessing direct podocalyxin protein in whole urine with a self-developed ELISA kit (9).…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in WT-1 staining have been used to confirm podocyte injury in biopsies (23). Urinary WT-1 mRNA was significantly increased in patients with diabetic nephropathy and chronic glomerulonephritis but was undetectable in normal volunteers (13). Lee et al (14) reported that urinary exosomal WT-1 was detected in 25 of 40 patients with active childhood nephrotic syndrome, but no difference in exosomal WT-1 was observed between focal segmental glomerulosclerosis (FSGS; n ϭ 7) and "non-FSGS" (n ϭ 18, not all of whom underwent kidney biopsy).…”
Section: Glomerular Diseases Including Hypertension and Diabeticmentioning
confidence: 99%
“…The majority of the biomarkers were assayed by immunoassays, primarily ELISA. The strategies to determine urinary mRNA profiles, such as in the studies of podocyte-associated molecules (podocalyxin, synaptopodin, α-actinin-4, podocin) [25, 28] and expression levels such as TNF-α [79], by reverse transcription polymerase chain reaction (RT-PCR) may be limited by the susceptibility for mRNA degradation by the presence of RNAses The analysis of biomarkers of renal injury in urinary exosomes represents an alternative approach. Exosomes can be recovered from the urine by differential centrifugation as a low-density membrane fraction.…”
Section: Resultsmentioning
confidence: 99%
“…In the mature glomerulus, the expression of WT1 is limited to podocytes. Kubo et al first reported the detection of endogenous WT1 mRNA in the urine of patients with renal diseases, including DN [28]. More recently, WT1 protein in urinary exosomes was isolated from spot urine samples of patients with type 1 diabetes, and higher levels were associated with significant increases in the urine protein-to-creatinine ratio, albumin-to-creatinine ratio and serum creatinine levels, as well as a decline in estimated glomerular filtration rate (eGFR) [21].…”
Section: Biomarkers Of Glomerular Damagementioning
confidence: 99%
“…The WT1 gene is highly expressed in mature podocytes as well. WT1 is down-regulated in a variety of glomerular diseases with podocyte injury [9], and WT1 mRNA is detected in the urine of some patients with glomerular diseases [10].…”
Section: Discussionmentioning
confidence: 99%